Dehydrobruceine C, A New Quassinoid from the Seeds of Brucea javanica - Li, Jun; Zheng, Dayong; Sun, Yukun; Sun, Yunfeng; Liu, Li; Fan, Ying; Zhang, Lide (Letters in Organic Chemistry, 2017)
Background: The seeds of Brucea javanica are known to be an abundant source of quassinoids, which have a structurally diverse and wide spectrum of biological effects, such as potential antiinflammatory, antitumor, antimalarial, antiamebic, and cytotoxic activities. However, only several dehydro-quassinoids were isolated and identified in this plant. Methods: The EtOAc extract of the seeds of B. javanica was submitted to silica gel CC, ODS, Sephadex LH-20, and RP-HPLC to get four compounds. Their chemical structures were elucidated by spectroscopic methods including UV, IR, 1D-NMR, 2D-NMR, and HR-MS. The inhibitory effects of 1-4 on nitric oxide (NO) production in lipopolysaccharide-activated macrophages were also evaluated. Results: A new dehydro-quassinoid namely, dehydrobruceine C (1), along with bruceine B (2), bruceine C (3), and bruceantinol (4) were separated from the EtOAc extract of the seeds of B. javanica. Compounds 1-4 displayed different intensity inhibitory effects on NO production, and their IC50 values were 33.11, 26.83, 9.08 and 8.25 μM, respectively, compared to indomethacin. Conclusion: B. javanica has been proven to contain structurally diverse and biologically active quassinoids. This is the first report on the isolation and chemical structure identification of dehydrobruceine C (1), this new quassinoid compound exhibited moderate anti-inflammatory activities in vitro.
Keywords: Brucea javanica